ANALISIS PENGARUH LIKUIDITAS, STRUKTUR AKTIVA, FREE CASH FLOW, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN UTANG (DER) PADA PT JASA MARGA Tbk PERIODE 2009-2018 - Anita Kristina; Prihatiningsih Prihatiningsih; Ida Savitri Kusmargiani (KEUNIS, 2019)
This research is based on the problems of the company PT Jasa Marga Tbk which has a problem with the performance of the company which is indicated by the DER of companie increased during the period 2009-2018. The purpose of this research is to analyze the influance of direction and significance of Liquidity, Asset Structure, Free Cash Flow and Company Size on Debt Policy (DER) in PT Jasa Marga Tbk for the period 2009-2018. The population and sample in this study were PT Jasa Marga Tbk. The analysis model used in this study is a multiple linear regression model. The results of the multiple linear regression analysis showed that (1) the influance of Liquidity (CR) on Debt Policy (DER) was positive and significant (2) the influance Asset Structure on Debt Policy (DER) was negative and not significant (3) the influance of Free Cash Flow on Debt Policy (DER) is positive and significant (4) the influance of Company Size on Debt Policy (DER) is positive and significant.